HUBUNGAN SIKAP DENGAN PERILAKU KARYAWAN DALAM KELOMPOK PADA KANTOR PERWAKILAN BKKBN PROVINSI SUMATERA UTARA - bukti Hartono sijabat (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT Relationship Between Employee Attitudes  With The Behavior Of Employees In The Group In BKKBN of North Sumatera Province Office The purpose of this study was to determine how the relationship between attitudes to the behavior of employees in the BKKBN Provinsi Sumatera Utara office. The data used in this study is the primary data and secondary data. Primary data collected through questionnaires distributed to the employees of BKKBN Provinsi Sumatera Utara office as many as 86 peoples. The analytical method used is descriptive quantitative correlation by using spearman rank. In the results based on corelation analysis showed that there is a positive relationship between employee attitudes (overall) with the behavior of employees in the group.  Overall  that there is a  relationship between employee attitudes  with the behavior of employees in the group with trust degree at 90 % with the value 0.756. Keywords: Employee Attitudes,  Behaviour Group